1987
DOI: 10.1111/j.1365-2265.1987.tb01163.x
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term Treatment of Hyperprolactinaemia With Bromocriptine: Effect of Drug Withdrawal

Abstract: Fifty-one patients with hyperprolactinaemia (23 with macroadenoma, 23 with microadenoma, and five with idiopathic hyperprolactinaemia) were treated with bromocriptine for 2-12 years (4.9 +/- 2.9 years, mean +/- SD). During therapy, the serum PRL levels were suppressed into the normal range in all but five patients. In these five patients, despite the high circulating PRL, gonadal function returned to normal in three, while in the other two gonadotrophin reserve was impaired even before therapy. Gel chromatogra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
2
1

Year Published

1991
1991
2011
2011

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(25 citation statements)
references
References 12 publications
2
20
2
1
Order By: Relevance
“…Of the 30 patients whose PRL levels fell to normal levels, 21 maintained the condition with low-dose bromocriptine (0.625-10 mg/d), and their PRL levels and tumor volumes were well controlled. According to the reports of bromocriptine withdrawal [32][33][34][37][38], 14 patients with normal PRL level and absent tumor on MR images withdrew from bromocriptine treatment in our group, and renewed tumor growth and recurrent hyperprolactinemia were not found during an average period of 1.5-year follow-up. About 18 patients with residual tumor invading the cavernous sinus had no related compromising symptoms, of which seven patients maintained normal PRL levels with low-dose bromocriptine treatment.…”
Section: Bromocriptine Reduction or Withdrawalcontrasting
confidence: 47%
See 1 more Smart Citation
“…Of the 30 patients whose PRL levels fell to normal levels, 21 maintained the condition with low-dose bromocriptine (0.625-10 mg/d), and their PRL levels and tumor volumes were well controlled. According to the reports of bromocriptine withdrawal [32][33][34][37][38], 14 patients with normal PRL level and absent tumor on MR images withdrew from bromocriptine treatment in our group, and renewed tumor growth and recurrent hyperprolactinemia were not found during an average period of 1.5-year follow-up. About 18 patients with residual tumor invading the cavernous sinus had no related compromising symptoms, of which seven patients maintained normal PRL levels with low-dose bromocriptine treatment.…”
Section: Bromocriptine Reduction or Withdrawalcontrasting
confidence: 47%
“…Some studies showed maintenance of normoprolactinemia and absence of adenoma reexpansion after BRC withdrawal in patients on long-term treatment for prolactinomas [13,16,[31][32][33]. Passos [34] reported that 131 cases of prolactinomas withdrew from drug treatment after an average period of 44 months of bromocriptine treatment, and 15.9% of macroprolactinomas had normal PRL level with no renewed tumor growth during the 44-month period of follow-up after their drug withdrawal.…”
Section: Bromocriptine Reduction or Withdrawalmentioning
confidence: 96%
“…After withdrawal of bromocriptine (Table 8), remission rates have been reported from as low as 0 to 9% (337)(338)(339)(340) to as high as 20 to 44% (97,125,(341)(342)(343)(344). In the only study restricted to patients with macroprolactinomas, van't Verlaat and Croughs (345) reported a remission rate in 8% of 12 patients after 12 months.…”
Section: B Bromocriptine Withdrawalmentioning
confidence: 94%
“…On the contrary, prolonged suppression of a PRL secreting adenoma leads to permanent cure in many cases and PRL is shown to remain low after discontinuation of long-term bromocriptine administration [34,35].…”
Section: Discussionmentioning
confidence: 99%